2006
DOI: 10.2337/db05-1285
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones Ameliorate Diabetic Nephropathy via Cell Cycle–Dependent Mechanisms

Abstract: Thiazolidinediones are ligands for peroxisome proliferator-activated receptor (PPAR)-␥, widely used as insulin sensitizer in type 2 diabetic patients and implicated in apoptosis, cell proliferation, and cell cycle regulation. Here, the effect of thiazolidinediones on G1-phase cell cycle arrest, the hallmark in diabetic nephropathy, was investigated. Eight-week-old male Otsuka Long-Evans Tokushima fatty rats were treated with pioglitazone (1 mg ⅐ kg body wt ؊1 ⅐ day ؊1 ) until 50 weeks of age and compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 43 publications
5
70
0
Order By: Relevance
“…revealed that gene expressions of podocyte structure-related genes as well as that of oxidative stress and lipid metabolism were restored concomitant with attenuation of albuminuria by PIO treatment (35). Previous study proved that pioglitazone could suppress high glucose-induced phosphorylation of p44/42 mitogen-activated protein kinase and reduce Bcl-2 and p27 (Kip1) protein levels in type 2 diabetes (36). Additionally, thiazolidinediones were found to modulate the glucocorticoid pathway and to exert direct protective effects on podocytes, similar to glucocorticoids (37).…”
Section: Discussionmentioning
confidence: 99%
“…revealed that gene expressions of podocyte structure-related genes as well as that of oxidative stress and lipid metabolism were restored concomitant with attenuation of albuminuria by PIO treatment (35). Previous study proved that pioglitazone could suppress high glucose-induced phosphorylation of p44/42 mitogen-activated protein kinase and reduce Bcl-2 and p27 (Kip1) protein levels in type 2 diabetes (36). Additionally, thiazolidinediones were found to modulate the glucocorticoid pathway and to exert direct protective effects on podocytes, similar to glucocorticoids (37).…”
Section: Discussionmentioning
confidence: 99%
“…Both PPAR␣ and -␥ agonists have been shown to be potentially therapeutic agents in treating diabetic nephropathy (7)(8)(9)(10). However, little is known about the efficacy of PPAR␣ and -␥ dual activators on renal complications in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…MES13 cells, glomerular mesangial cells from an SV40 transgenic mouse, were grown as previously described [22]. mProx24 cells, a murine renal proximal tubular epithelial cell line derived from the kidney of an adult C57BL/6J mouse [23], were cultured in Dulbecco’s modified Eagle’s medium (Sigma-Aldrich, St. Louis, Mo., USA) supplemented with 5.5 m M D -glucose, 10% fetal bovine serum, 100 U/ml penicillin, and 100 mg/ml streptomycin at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%